Ultrasound Imaging Guide for Assessment of the Intrinsic Ligaments Stabilizing the Subtalar and Midtarsal Joints - Zaottini, Federico; Picasso, Riccardo; Pistoia, Federico; Perez, Maribel Miguel; Möller, Ingrid; Rossi, Federica; Bruns, Alessandra; Tagliafico, Alberto Stefano; Martinoli, Carlo (Seminars in Musculoskeletal Radiology, 2020)
Ligament injuries around the subtalar, talocalcaneonavicular, and calcaneocuboid joints are often underestimated on clinical and imaging findings during investigation of patients with ankle and foot injuries. Because a delayed diagnosis of midtarsal ligament tears may lead to chronic pain and functional disability, an in-depth knowledge of the complex regional anatomy and of the appropriate ultrasound scanning technique is a prerequisite for evaluating these structures and avoiding misdiagnoses. The objective of this article is twofold: to describe the relevant anatomy and biomechanics related to the ligaments that stabilize the subtalar, talocalcaneonavicular, and calcaneocuboid joints, and to illustrate reasoned landmark-based scanning techniques to provide a systematic examination of these ligaments and thus make ultrasound an effective tool for assessment of patients with suspected subtalar or midtarsal sprain.
Keywords: calcaneocuboid joint ligaments; inferior extensor retinaculum; subtalar joint ligaments; talocalcaneonavicular joint ligaments; ultrasound